ARTISTIC AND COMPOSITIONAL FEATURES OF THE USE OF VINTAGE STYLE ELEMENTS IN MODERN CLOTHES DESIGN - Ніколаєва, Т. В.; Гаиова, І. Л.; Давиденко, І. В. (Art and Design, 2019)
Research of historical experience and modern trends of the vintage tendencies in design of clothing and accessories, determining methods for creative transformation of materials’ surfaces and decorative elements to be used in forward-looking fashion collections. Scientific research uses modern methods of historiographical, literary and analytical, system-structural analysis as well as methods of classification of the artistic and compositional transformation means applied to decorative elements and complements to costume. The study of the historical background of vintage style and promising directions of its development was done. The analysis of the use of vintage elements in modern clothes was performed. The assortment of decorative elements and costume additions of various fashion styles of the 20th century was analyzed. Technology of material processing for creating vintage effects in a modern costume was considered. The presented research results have some scientific novelty in coverage of the genesis of vintage style development and perspective directions of the further development of the use of elements of vintage in modern clothes, as well as the classification of means for achieving the effect of vintage materials and additions to the costume. Practical significance. The results of scientific work can be used in the training process of designers-stylists and practical activities of contemporary artists, designers and fashion-designers. As a result of the research a modern collection of accessories was created.